Study of symbol for the Kasunanan Surakarta Palace through the Spradley Ethnography Approach / IF Bambang Sulistyono ... [et al.] - Sulistyono, IF Bambang; Purwasito, Andrik; Warto, Warto; Pitana, Titis Srimuda (Universiti Teknologi MARA, Perak, 2022)
Hadiningrat said that the Kasunanan Surakarta was a fraction of Islamic Mataram when the Giyanti Agreement was approved. Historically, since the transfer movement of the capital Islamic Mataram Kingdom from Kartasura to Surakarta, the name of Keraton Surakarta Hadiningrat was turn up. This incident can be used as a benchmark for the presence of the palace symbol from the running of the government. Ethnography does not only study about society, but also learns from society (Spradley, 1980: 2). In this research, the theoretical approach that used to interpret and analyze the pattern of the Kasunanan Surakarta symbol is through the six ethnographic levels of James P. Spradley.